2006
DOI: 10.1161/01.atv.0000219233.31702.c9
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 Microsatellite Polymorphism and Susceptibility to Carotid Arteries Atherosclerosis

Abstract: The number of repeats (> or =22 CA) in the microsatellite of MMP-9 promoter, but not MMP-9 plasma levels, is associated to carotid atherosclerosis and particularly to plaques with a thin fibrous cap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 34 publications
1
13
0
6
Order By: Relevance
“…Recently, several lines of researches have showed that MMP-9 plays an important role in atherogenesis by promoting degradation of the extracellular matrix [18,19]. Within the vulnerable atheromatous plaques, particularly in the inflamed shoulder and fibrous caps, there exists strong MMP-9 expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several lines of researches have showed that MMP-9 plays an important role in atherogenesis by promoting degradation of the extracellular matrix [18,19]. Within the vulnerable atheromatous plaques, particularly in the inflamed shoulder and fibrous caps, there exists strong MMP-9 expression [20].…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding vascular adhesion molecules, matrix metalloproteinases (MMPs), and interleukins are all downstream targets of NF-κB. Genetic polymorphisms at the MCP-1 (17), MMP-3 (18,19), MMP-9 (20) and interleukin-6 (IL-6) (21) genes were found to be associated with carotid atherosclerosis. In our previous study (7), BRAP was found to be involved in the NF-κB-dependent inflammatory pathway.…”
mentioning
confidence: 99%
“…High genetic variability was observed (k = 13), even higher than that reported for African-American populations (k = 11) (Ferrand et al, 2002). This diversity was stronger in the Mestizo population, which exhibited the most frequent alleles of European (CA 14 ), Asian (CA 21 ), and African-American (CA >21 ) populations, as well as significant heterogeneity (6%, P ≤ 0.0001) (Ferrand et al, 2002;Fiotti et al, 2006;Lee et al, 2010). These findings were corroborated with PCA and genetic distance analyses, which showed relative proximity between the Mestizo population and their historical parental populations (Asian, European, and African) (Salazar-Flores et al, 2010).…”
Section: Discussionmentioning
confidence: 74%
“…Studies on the MMP-9 gene have associated the length of the dinucleotide repeat with promoter activity, suggesting that (CA) 14 may cause a significant decrease (up to 50%) in transcriptional activity in comparison to (CA) 21 (Shimajiri et al, 1999;Ferrand et al, 2002). Therefore, polymorphisms of the MMP-9 gene have been implicated in the susceptibility to various diseases such as cancer (Kader et al, 2006), lipid levels (Mazzotti et al, 2014), cardiovascular diseases (Fiotti et al, 2006), and Alzheimer's disease (Flex et al, 2013), among others.…”
Section: Introductionmentioning
confidence: 99%